The Dead Sea scrolls translated : the Qumran texts in English - Martinez, Florentino Gfrey50(Editor; Garcia Martinez, Florentino (Leiden ; New York : Grand Rapids : E.J. Brill ; W.B. Eerdmans, 1996)
This is the most comprehensive one volume edition of the Dead Sea Scrolls ever attempted. Martinez has prepared a careful rendering into English of everything worth translating, including the full texts of the multiple copies of works such as the Community Rule and the Damascus Document. Especially helpful is the fact that the line numbers are specified in the text so that the reader knows exactly where the words are found. The substantial introduction and the full ist of Qumran manscripsts, with biographical references, enhance the value of the this volume even more.
Translation of: Textos de Qumran.
Keywords: Ancient writings - Religious. -- Translation - Ancient religous writings